Toward a methodology for exploring mathematics preservice teachers' learning from a sociocultural perspective (2009)
This paper describes a methodological procedure for characterizing mathematics preservice teachers' learning from a sociocultural perspective. The procedure involves interpreting some aspects of Wenger's theory of social learning, adapting them to preservice teacher training, and making this adaptation operational for coding and analyzing audio recordings of a group of preservice teachers working at home. An example of a research result obtained using this procedure is presented.